Flavonoid, Phenolic and Antioxidant Content in Several Parts of the Artemisia Plant - Yefrida; Yola Tsurayya Putri; Refilda (Jurnal Kimia Unand, 2025)
Free radicals can cause damage to cells in the body. This can be prevented or treated by using substances that are antioxidants. Artemisia plants (Asteraceae family) are one of the potential sources of natural antioxidants. This study was conducted to determine the content and correlation of flavonoids, phenolics and antioxidant activity of leaves, stems and roots of four types of Artemisia genus plants. The method used for the determination of total flavonoid content was the AlCl3 method and the Folin-Ciocalteau method for the determination of total phenolic content. Antioxidant activity was determined by DPPH methods. Based on this study, with the exception of Artemisia vulgaris plants, the antioxidant activity was determined by DPPH and MPM methods., which had the highest quantity in the roots, the leaves contained the highest levels of flavonoids and total phenolics relative to other sections. The data obtained were further tested with ANOVA which showed a significant difference between flavonoid content, phenolic content, and antioxidant activity with plant type and plant part.